Characterization and confirmation of the long lifetime of a-decade-aged hydroxyapatite ceramic electrets - Kosuke Nozaki; Kazuaki Hashimoto; Noriyuki Wakabayashi; Kimihiro Yamashita (Scientific Reports)
Abstract With an aim at long-time use of biocompatible hydroxyapatite (HAp) ceramic electrets as implant devices in-vivo, long-term tracking experiments involving non-destructive surface potential (VS) measurements over a decade were undertaken to confirm the long lifetime (LT) of HAp ceramic electrets. A-decade-aged HAp electrets maintained their initial as-polarized VS of ~ 100 V on storage in an oven at warm temperatures (such as 60 ℃). In contrast, the VS of electrets preserved in air at room temperature gradually reduced after 8 years of aging, retaining the as-polarized value on exposure to heating at 200 ℃; this phenomenon can be ascribed to the shielding effect of moisture on the specimen surface. The long LT of HAp electrets was also confirmed by a destructive measurement technique involving thermally stimulated dissipated currents (TSDC) on decade-aged specimens. Besides confirming the semipermanent LT of HAp ceramic electrets, this study proposes the concept of a grain electret to explain the non-identical surface charge density values derived from VS and TSDC data. Therefore, this study could open new frontiers in ceramic electret research, paving the way for the widespread practical application of such systems.